2013
DOI: 10.1111/bjd.12129
|View full text |Cite
|
Sign up to set email alerts
|

Skin tumours in the West of Scotland renal transplant population

Abstract: This is the first study of skin cancer in prevalent Scottish RTRs. The incidence of skin cancer is high and appears to have a direct relationship to the overall burden of immunosuppression. The SCC:BCC ratio, which is lower than reports from other centres, deserves further scrutiny.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…The fact that cumulative dosage of cyclosporine and other immunosuppressants is independently associated with risk of non-cutaneous cancers in OTRs tends to support this theory 19,20 . The best example of the association between immunosuppression and increased skin cancer risk comes from patients with human immunodeficiency virus (HIV) and acquired immunodeficiency syndrome (AIDS).…”
Section: Skin Cancer In Organ Transplant Recipientsmentioning
confidence: 93%
“…The fact that cumulative dosage of cyclosporine and other immunosuppressants is independently associated with risk of non-cutaneous cancers in OTRs tends to support this theory 19,20 . The best example of the association between immunosuppression and increased skin cancer risk comes from patients with human immunodeficiency virus (HIV) and acquired immunodeficiency syndrome (AIDS).…”
Section: Skin Cancer In Organ Transplant Recipientsmentioning
confidence: 93%
“…OTRs rely on immunosuppressive drug therapy to ensure the long‐term survival and function of their transplanted organs. The use of multiple immunosuppressive drugs in combination and the necessity for long periods of immunosuppression has led to an increased incidence of NMSC formation . Indeed, malignancy is now the commonest cause of death in renal transplant patients in Australia .…”
Section: Nmsc Risk Is Associated With Immunosuppression Regimementioning
confidence: 99%
“…The use of multiple immunosuppressive drugs in combination and the necessity for long periods of immunosuppression has led to an increased incidence of NMSC formation. [10][11][12][13] Indeed, malignancy is now the commonest cause of death in renal transplant patients in Australia. 14 Reducing immunosuppression may reduce the risk of skin cancer development, but needs to be counterbalanced by the increased risk of allograft rejection.…”
Section: Nmsc Risk Is Associated With Immunosuppression Regimementioning
confidence: 99%
“…The majority of included studies were deemed to be high quality (5,6,21,(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47). Ten were assessed as medium quality (2,3,7,20,(48)(49)(50)(51)(52)(53), and two were low quality (54,55) (Table S2).…”
Section: Quality Assessmentmentioning
confidence: 99%
“…Ten cohort studies and one clinic-based case-control study reported on the association between azathioprine risk and various other skin cancers. The risk of melanoma was evaluated in six studies (5,45,46,52,54,55), MCC in three (6,52,54), KS in five (20,46,49,52,53) and other rare skin cancers (e.g. atypical fibroxanthoma, B cell lymphoma) in four studies (20,45,52,54).…”
Section: Risk Of Other Skin Cancersmentioning
confidence: 99%